Reducing Patients’ Death Rate Through Rapid Response Team Bell Activation in Emergency Room - Nurul Ardlianawati; Taufiqul Rochman; Aang Kunaifi; Emha Rafi Pratama (Journal of Nursing Science Update (JNSU), 2022)
The patient death rate in the emergency department is a critical measure of the quality of hospital services and is regulated by legislation. The presence of a rapid response team is one of the factors influencing the fatality rate. A bell is a gadget that can summon a quick response team during the resuscitation process. The specific purpose of this research was to determine the effectiveness of the activation of the bell in the emergency room resuscitation of Universitas Airlangga Hospital on the patient death rate. The research design is a comparative study with a retrospective approach. Researchers used total sampling with a population of all patients in the emergency resuscitation room at Universitas Airlangga Hospital from July-December 2019 that met the criteria. The design of this study compared two groups that were extracted from the electronic register. The data were divided into two groups: three months before the intervention of the bell (N=62) and three months after the activation of the bell (N=65). The statistical analysis result of the Chi-Square Test obtained a p-value < 0.05 for the death rate between the two groups. There is a significant reduction in the death rate before and after the intervention. The result shows that it is possible to reduce the death rate by using a bell as a method to activate the rapid response team in the emergency room during resuscitation. This study offers a simple way to improve the death rate in the emergency room using bell intervention.